(untitled) (Third Sector Social Economic Review, 2020)
This article was tried to answer the question of possible future of nation states and how globalization process will be followed in the fight against epidemic term. With introduction of Covid-19 to world agenda, there have been some important economic contractions that virus has entered states and governments have various measures to prevent these contractions from this situation into an economic crisis. While some of these measures have been taken place in cooperation with other countries, other measures are to close borders to protect citizens, cash to citizens of their state, such as in Turkey has been found in-kind assistance. In this direction, governments around world have tried to find answers to questions of what kind of global system which they follow. Whether USA, France, Italy, Turkey, China, South Korea, Singapore, Taiwan are successful states in the fight against epidemic are examined in this article. Along with global system and possible future of the nation state connected to success and failures in combating epidemic. Covid-19 was evaluated in the context of political and social consequences of epidemic.